ISOLATION OF SITOSTEROL AND STIGMASTEROL FROM THE ROOTS OF CROTON PENDULIFLORUS - Ferdinand, C.; Isyaka, M. Sani; Adelakun, Tiwa A.; Ibekwe, N. N.; Igoli , John; Abdullahi, Abdullahi M. (FUDMA JOURNAL OF SCIENCES, 2023)
The primary aim of this study was to isolate Sitosterol from the root of Croton Penduliflorus. Croton Penduliflorus Hutch (Euphorbiaceae) commonly known as Turk’s Cap though to originate from Malaysia, is a tropical evergreen plant widely distributed in the southern part of Nigeria. It is employed in folklore medicine both as drastic and fugitive, as well as a psychotropic medicinal plant. It is also credited with antimicrobial, antivenom, antiparalytical, rubefacient and anti-tumor potencies Extraction of the roots of Croton Penduliflorus with ethanol and partitioning of the extract with hexane, chloroform and ethyl acetate followed by column chromatography of the chloroform extract has led to the isolation of sitosterol, stigmasterol and a substituted benzene derivative. Their structures were established using 1D and 2D NMR, LCMS, and FTIR spectral analysis and a comparison of their spectral data with literature reports.